AKTIVITAS ANTIBAKTERI EKSTRAK TEMPE TERHADAP BAKTERI Bacillus subtilis DAN Staphylococcus aureus [Antibacterial Activity of Tempe Extracts on Bacillus subtilis and Staphylococcus aureus] - D. Elysa Putri Mambang; - Rosidah; Dwi Suryanto (Jurnal Teknologi dan Industri Pangan, 2014)
AKTIVITAS ANTIBAKTERI EKSTRAK TEMPE TERHADAP BAKTERI Bacillus subtilis DAN Staphylococcus aureus [Antibacterial Activity of Tempe Extracts on Bacillus subtilis and Staphylococcus aureus]D. Elysa Putri Mambang1)*, Rosidah1) dan Dwi Suryanto2)1) Program Studi Magister Farmasi Fakultas Farmasi, Universitas Sumatera Utara, Medan2) Departemen Biologi Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Sumatera Utara, Medan Diterima 13 Agustus 2013 / Disetujui 05 Februari 2014ABSTRACT  Tempe is a soybean fermented product by Rhizopus oligosporus which contains high amounts of bioactive compounds including antibacterial compounds. The aim of this research is to observe the antibacterial activity of tempe extract against Bacillus subtilis and Staphylococcus aureus. The results of this research broadens the current knowledge of tempe as functional food. Samples of commercial tempe were obtained from a traditional market of Pringgan Medan, Sumatera Utara. Tempe samples were then extracted using three solvents with different polarity: ethanol, n-hexane and ethyl acetate, each at three levels of concentration i.e. 300 mg/mL (30%), 400 mg/mL (40%) and 500 mg/mL (50%). The antibacterial activity test of tempe extracts was carried out using disc difussion method on Mueller Hinton Agar (MHA), and incubation was conducted at 36-37°C for 24 hrs. The obtained data were tested statistically with Analysis of Variant (ANOVA) p>0.05. The ethanol and ethyl acetate extracts of tempe inhibited the growth of B. subtilis and S. aureus. Meanwhile, the ethyl acetate extract of tempe at concentration of 500 mg/mL had the highest inhibition against S. aureus as shown by inhibition diameters of 15.50±0.44 mm (p>0.05), and B. subtilis at 14.13±0.21 mm (p>0.05). No inhibition observed with the n-hexane extracts of tempe against the above bacteria.